Cuantificacion de biomasa y reserva de carbono en dos sistemas de produccion de cacao(tehobroma cacao L. en el campo experimental el choclino ,Banda de Shilcayo - San Martin - Bartra Reategui, Christian Robin (2011)
QUANTIFYING BIOMASS AND CARBON BOOK TWO OF COCOA PRODUCTION SYSTEMS (Theobroma cacao L.) IN THE EXPERIMENTAL FIELD CHOCLINO BANDA DE SHILCAYO - SAN MARTÍN” The development of a new international market for environmental services (carbon sequestration) has been derived from the need to reduce global emissions of gases that contribute to "greenhouse effect". The aim of this paper is to quantify the amount of biomass and carbon in two systems of production of cocoa ( Theobroma cacao L.), system of forest management raleado (SMBR) and the traditional management system (GTS), associated with species Forestry, to analyze the data we used nonparametric statistics. Runs on the province and department of San Martín, geographically located South Latitude 06 º 28'37 .3 "West Longitude 76 º 19'54 .6", 506 msnmm altitude, soil reaction presents moderately acidic, with pH of 5.42 to 6.26 . . The results show that the total carbon obtained by the system of forest raleado in cocoa production was 187.55 ± 24.49 t ha -1 and the total carbon obtained by the traditional system (Rozo, slash and burn) from Cocoa product ion was 139.36 ± 12.33 t ha -1 .The parameter provides the most amount of carbon stored in both production systems with the ground was 129.29 ± 11.45 t ha -1 for the system of forest management raleado and 117.52 ± 12.85 t ha -1 to the traditional management system.